2011
DOI: 10.1007/s10653-011-9375-5
|View full text |Cite
|
Sign up to set email alerts
|

Increasing trend of primary NO2 exhaust emission fraction in Hong Kong

Abstract: Despite the successful reduction in roadside NO( x ) levels, no such decrease has been detected in roadside NO(2) concentration in Hong Kong. One underlying cause could be the rising primary NO(2) fraction of the total emission of NO( x ). Primary NO(2) can be particularly detrimental to Hong Kong because a large fraction of the population are exposed to the traffic-related primary pollutants in the street can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 25 publications
5
15
0
Order By: Relevance
“…Other epidemiology studies also reported on NO 2 as the source derived from outdoor environment Rosenlund et al, 2009;Lamsa et al, 2013), which mostly indicates urban area. It was suggested that in urban area, motor vehicle emissions are the major source of NO 2, which was also found in other studies that investigated the different levels between study areas (Tian et al, 2011;Wichmann et al, 2010).…”
Section: Had Done Two Times Measurement In 2008supporting
confidence: 70%
“…Other epidemiology studies also reported on NO 2 as the source derived from outdoor environment Rosenlund et al, 2009;Lamsa et al, 2013), which mostly indicates urban area. It was suggested that in urban area, motor vehicle emissions are the major source of NO 2, which was also found in other studies that investigated the different levels between study areas (Tian et al, 2011;Wichmann et al, 2010).…”
Section: Had Done Two Times Measurement In 2008supporting
confidence: 70%
“…7). This finding was supported by the Hong Kong emission inventory, which indicated that the NO x emission decreased from 1997 to 2014 in Hong Kong (HKEPD, 2016), and studies conducted by Tian et al (2011) and Lau et al (2015), who found an increasing trend of primary NO 2 emission in Hong Kong due to several diesel retrofit programmes in the period 1998-2008. Apart from the regional and local impact on O 3 trends, the impact of variations of baseline O 3 was also considered. Oltmans et al (2013) reported that O 3 at mid-latitudes of the Northern Hemisphere was flat or declining during the period 1996-2010 and the limited data in the subtropical Pacific suggested very little change during the same period.…”
Section: Long-term Trends Of Locally Produced O 3 and Regional Contrimentioning
confidence: 65%
“…The reduction of NO titration was also confirmed by the increasing NO 2 / NO x ratio at a roadside site (Mong Kok) in Hong Kong. The NO 2 / NO x emission ratio is a parameter that can be used to examine the variation of NO titration (Carslaw, 2005;Yao et al, 2005;Dallmann et al, 2011;Tian et al, 2011;Ning et al, 2012;Lau et al, 2015). Generally, higher ratios of NO 2 / NO x mean a lower potential of O 3 titration by NO, resulting in higher O 3 .…”
Section: Long-term Trends Of Locally Produced O 3 and Regional Contrimentioning
confidence: 99%
“…In Hong Kong, vehicle emissions are the main source of NO x . Similar to many metropolitan areas, a decreasing trend of ambient and roadside NO x levels has been observed (Carslaw, 2005;Keuken et al, 2009;Tian et al, 2011) which is contributed from the effective vehicular emission control measures in the past. However, the pollution levels measured at both ambient and roadside air quality monitoring stations are still occasionally exceeded the of NO x is recorded at the roadside monitor stations in Hong Kong, which means the reduction rate of NO 2 is slower than NO in recent years (Tian et al, 2011).…”
mentioning
confidence: 76%
“…Similar to many metropolitan areas, a decreasing trend of ambient and roadside NO x levels has been observed (Carslaw, 2005;Keuken et al, 2009;Tian et al, 2011) which is contributed from the effective vehicular emission control measures in the past. However, the pollution levels measured at both ambient and roadside air quality monitoring stations are still occasionally exceeded the of NO x is recorded at the roadside monitor stations in Hong Kong, which means the reduction rate of NO 2 is slower than NO in recent years (Tian et al, 2011). Vehicular NO 2 is either primarily emitted at the tail pipe or secondarily formed from oxidation of NO emission involving ozone and volatile organic compounds (VOCs) in the ambient (Muilwijk et al, 2016; 4.13 km Avantes spectrometer (AvaSpec-ULSi2048L-USB2) with a Sony ILX511 charge coupled device (CCD) detector.…”
mentioning
confidence: 76%